Prognosis of hospitalized children under 2 years of age with co-detection of influenza A and respiratory syncytial virus at the healthcare facility - Elisa Teixeira Mendes; Hadassa L. Paranhos; Isabela C. M. Santos; Lais Bomediano de Souza; José Luis Braga de Aquino; Vania Aparecida Leandro-Merhi; Raquel Vieira da Silva; Maria Patelli J. S. Lima (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: the aim of this study is to evaluate the impact of co-detection of Flu A and RSV using rapid immunochromatographic tests at the point of care, in pediatric patients under 2 years of age in a general hospital. Methods: a retrospective cohort study was conducted to analyze clinical outcomes in hospitalized infants with viral respiratory disease with positive results of rapid immunochromatographic test for RSV and/or Flu-A, from 2013 to 2018. A logistic regression model was adjusted to analyze predictors of orotracheal intubation during hospitalization. Results: we analyzed 220 cases: RSV (192), Flu-A (9), co-detection (19). Lethality rate was 1.8% (2 cases), and 88% (194) were under 1 year of age. Mean time of hospitalizations was higher in patients with co-detection. Variables significantly associated with orotracheal intubation were: younger age in months, comorbidities, RSV and Flu-A co-detection, and bacterial pneumonia during hospitalization. Conclusions: RSV and Flu-Aco-detection was associated with the least favorable clinical prognoses in this study. Rapid test diagnosis may provide important information at the point of care, because molecular panels are not widely accessible in general hospitals. Rapid diagnosis allows timely evaluation and treatment.